Specifying Executable Platform-Independent Models using OCL - Kelsen, Pierre; Pulvermueller, Elke; Glodt, Christian (Electronic Communications of the EASST, 2007)
Model-driven architecture aims at describing a system using a platform-independent model in sufficient detail so that the full implementation of the system can be generated from this model and a platform model. This implies that the platform-independent model must describe the static structure as well as the dynamic behavior of the system. We propose a declarative language for describing the behavior of platform-independent models based on a hybrid notation that uses graphical elements as well as textual elements in the form of OCL code snippets. Compared to existing approaches based on action languages it is situated at a higher level of abstraction and, through a clean separation of modifier operations and query operations, simplifies the comprehension of the behavioral aspects of the platform-independent system.